2014
DOI: 10.1039/c4cp01428f
|View full text |Cite
|
Sign up to set email alerts
|

Quantum yield in blue-emitting anthracene derivatives: vibronic coupling density and transition dipole moment density

Abstract: A theoretical design principle for enhancement of the quantum yield of light-emitting molecules is desired. For the establishment of the principle, we focused on the S1 states of blue-emitting anthracene derivatives: 2-methyl-9,10-di(2'-naphthyl)anthracene (MADN), 4,9,10-bis(3',5'-diphenylphenyl)anthracene (MAM), 9-(3',5'-diphenylphenyl)-10-(3'',5''-diphenylbiphenyl-4''-yl) anthracene (MAT), and 9,10-bis(3''',5'''-diphenylbiphenyl-4'-yl) anthracene (TAT) [Kim et al., J. Mater. Chem., 2008, 18, 3376]. The vibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…The energy of T 4 state was higher than S 1 for all compounds except the mentioned 4a and 4b compounds where T 4 was situated below S 1 . The calculated oscillator strength of S 0 →S 1 transition was found to increase for compounds 1-4a/b (from 0.125 to 0.232 and from 0.097 to 0.229 for a compounds and b compounds, respectively) due to the conjugation extension [32] while a bit lower values were observed for compounds 5a/b and 6a/b (~0.2 and 0.16, respectively).…”
Section: Synthesismentioning
confidence: 85%
See 2 more Smart Citations
“…The energy of T 4 state was higher than S 1 for all compounds except the mentioned 4a and 4b compounds where T 4 was situated below S 1 . The calculated oscillator strength of S 0 →S 1 transition was found to increase for compounds 1-4a/b (from 0.125 to 0.232 and from 0.097 to 0.229 for a compounds and b compounds, respectively) due to the conjugation extension [32] while a bit lower values were observed for compounds 5a/b and 6a/b (~0.2 and 0.16, respectively).…”
Section: Synthesismentioning
confidence: 85%
“…However the additional π-conjugation extension towards the long axis of the molecule results in the reorganization of singlet and triplet energy levels when the T n level emerges below S 1 leading to the efficient ISC recombination and low Φ F [26]. Despite the importance of the intersystem crossing, recent studies have suggested that the vibrational relaxation may also be the important pathway for the non-radiative decay in anthracene derivatives [31,32]. Modification of anthracene core with various alkyl groups allows to obtain amorphous thin films, however those anthracene derivatives like 9,10-di(2-naphthyl)anthracene posses low hole drift mobility (μ h ) [33][34][35] of about 10 -7 -10 -5 cm 2 /Vs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this design principle also has certain drawbacks: (1) the small overlap between the HOMO and LUMO leads to suppression of the oscillator strength 9, 10 , and (2) TADF OLEDs exhibit broad emission wavelengths because of charge-transfer (CT) excitation. In order to overcome these drawbacks, Sato et al .…”
Section: Introductionmentioning
confidence: 99%
“…and Sato et al . have already designed and proposed iST molecules based on anthracene 9, 10 and perylene derivatives 11 , respectively.…”
Section: Introductionmentioning
confidence: 99%